Suzuki–Miyaura Reactions of 2,7-Dichloro-1,8-naphthyridine - Ehlers, Peter; Petrosyan, Andranik; Ghochikyan, Tariel V.; Saghyan, Ashot S.; Neubauer, Antje; Lochbrunner, Stefan; Langer, Peter (Synlett, 2013)
2,7-Diaryl- and 2,7-dialkenyl-1,8-naphthyridines were prepared in high yields by Suzuki–Miyaura reactions of 2,7-dichloro-1,8-naphthyridines. While most of the products proved to be not or only weakly fluorescent, we observed a strong fluorescence in case of 2,7-bis(4-methoxyphenyl)-1,8-naphthyridine containing two electron-donating aryl groups.
Keywords: catalysis; heterocycles; palladium; cross-coupling reactions; nitrogen